Extramitochondrial domain rich in carbonic anhydrase activity improves myocardial energetics. - Schroeder, M; Ali, M; Hulikova, A; Supuran, C; Clarke, K; Vaughan-Jones, R; Tyler, D; Swietach, P (2013)
CO2 is produced abundantly by cardiac mitochondria. Thus an efficient means for its venting is required to support metabolism. Carbonic anhydrase (CA) enzymes, expressed at various sites in ventricular myocytes, may affect mitochondrial CO2 clearance by catalyzing CO2 hydration (to H(+) and HCO3(-)), thereby changing the gradient for CO2 venting. Using fluorescent dyes to measure changes in pH arising from the intracellular hydration of extracellularly supplied CO2, overall CA activity in the cytoplasm of isolated ventricular myocytes was found to be modest (2.7-fold above spontaneous kinetics). Experiments on ventricular mitochondria demonstrated negligible intramitochondrial CA activity. CA activity was also investigated in intact hearts by (13)C magnetic resonance spectroscopy from the rate of H(13)CO3(-) production from (13)CO2 released specifically from mitochondria by pyruvate dehydrogenase-mediated metabolism of hyperpolarized [1-(13)C]pyruvate. CA activity measured upon [1-(13)C]pyruvate infusion was fourfold higher than the cytoplasm-averaged value. A fluorescent CA ligand colocalized with a mitochondrial marker, indicating that mitochondria are near a CA-rich domain. Based on immunoreactivity, this domain comprises the nominally cytoplasmic CA isoform CAII and sarcoplasmic reticulum-associated CAXIV. Inhibition of extramitochondrial CA activity acidified the matrix (as determined by fluorescence measurements in permeabilized myocytes and isolated mitochondria), impaired cardiac energetics (indexed by the phosphocreatine-to-ATP ratio measured by (31)P magnetic resonance spectroscopy of perfused hearts), and reduced contractility (as measured from the pressure developed in perfused hearts). These data provide evidence for a functional domain of high CA activity around mitochondria to support CO2 venting, particularly during elevated and fluctuating respiratory activity. Aberrant distribution of CA activity therefore may reduce the heart's energetic efficiency.